Potential Immunomodulatory Properties of Biologically Active Components of Spices Against SARS-CoV-2 and Pan β-Coronaviruses - Sengupta, Sourodip; Bhattacharyya, Debina; Kasle, Grishma; Karmakar, Souvik; Sahu, Omkar; Ganguly, Anirban; Addya, Sankar; Das Sarma, Jayasri (Frontiers in cellular and infection microbiology, 2021)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-induced COVID-19 has emerged as a defining global health crisis in current times. Data from the World Health Organization shows demographic variations in COVID-19 severity and lethality. Diet may play a significant role in providing beneficial host cell factors contributing to immunity against deadly SARS-CoV-2 pathogenesis. Spices are essential components of the diet that possess anti-inflammatory, antioxidant, and antiviral properties. Hyperinflammation, an aberrant systemic inflammation associated with pneumonia, acute respiratory failure, and multiorgan dysfunction, is a major clinical outcome in COVID-19. Knowing the beneficial properties of spices, we hypothesize that spice-derived bioactive components can modulate host immune responses to provide protective immunity in COVID-19. This study emphasizes that biologically active components of spices might alleviate the sustained pro-inflammatory condition by inhibiting the activity of tumor necrosis factor-alpha (TNF-α), interleukins (IL6, IL8), and chemokine (CCL2) known to be elevated in COVID-19. Spices may potentially prevent the tissue damage induced by oxidative stress and pro-inflammatory mediators during SARS-CoV-2 infection. The current study also highlights the effects of spices on the antioxidant pathways mediated by Nrf2 (nuclear factor erythroid 2-related factor 2) and Hmox1 (heme oxygenase 1) to restore oxidative homeostasis and protect from aberrant tissue damage. Taken together, the anti-inflammatory and antioxidant activities of bioactive components of spices may hold a promise to target the cellular pathways for developing antivirals against SARS-CoV-2 and pan β-coronaviruses.